Methods for constructing complex software systems based on software technology convergence: Web-Service Semantic, WebService and Agente, Multi-Agente - Mamesh S. , Mamesh S.; Bekzhigitova L., Bekzhigitova L. (Рroblems of engineering and professional education, 2023)
This article discusses the issues of information and communication technologies, educational electronic resources in the process of building complex software systems. Software for the development of the system reach a level of complexity that the existing approaches and concepts of software development are becoming ineffective. As a rule, it is born a new programming paradigm, which are gradually moving all developers. Creating the concept of procedural, modular and objectoriented programming - are examples of long-standing or recent past; the future, it seems, for the service-oriented architecture.